Pelatihan Artificial Intelligence (AI) untuk Meningkatkan Literasi Digital dan Kreativitas Siswa SMA Negeri 1 Srengat - Titik Lusiani; Sulistiowati; Tutut Wurijanto; Agus Dwi Churniawan; Sutikno (Jurnal Ragam Pengabdian, 2025)
The rapid development of Artificial Intelligence (AI) has drastically changed the world of schooling and digital innovation, especially for Generation Z. This community service program aims to improve digital literacy and creativity of students at SMA Negeri 1 Srengat through training in the use of AI, specifically the ChatGPT and Gemini applications. This program was implemented using interactive lecture methods, live demonstrations, and direct practice with digital devices. Evaluation was carried out using pre-tests, post-tests, and questionnaires. The evaluation results showed a 65% increase in participants' understanding of the training material, while the questionnaire obtained an average score of 3.6 (agree category), indicating that the training was effective and relevant to students' needs. This activity succeeded in fostering critical thinking skills, creativity in using AI technology, and awareness of ethical digital practices in students. In addition, this training contributed to strengthening students, especially in the aspects of critical reasoning, creativity, and independence. Therefore, this AI training is a strategic initiative to prepare the younger generation to be technologically literate, innovative, and adaptive in the digital era.